The limits of community policing: civilian power and police accountability in black and brown Los Angeles - Gascón, Luis Daniel (New York University Press, 2019)
Introduction -- Roots, rebellion, and reform -- The making of Lakeside -- Organizing the division -- Complaint encounters -- No place for mom-and-pop -- The politics of partnership -- Conclusion